Relating external load variables with individual tactical actions with reference to playing position: an integrated analysis for elite futsal - Ribeiro, J. N.; Yousefian, F.; Monteiro, D.; Illa, J.; Couceiro, M.; Sampaio, J.; Travassos, B. (International Journal of Performance Analysis in Sport, 2024)
The purpose of this study was to contextualise players` high-intensity activities (HIA) with individual tactical actions during match play with reference to playing positions. Tracking data was obtained using local positioning system devices from 19 male elite futsal players (28.8 ± 2.4 years). The HIA measures included high-intensity acceleration (ACC; =3 m · s-2), deceleration (DEC; =-3 m · s-2), and high-speed running (HSR; =18 km · h-1). Tracking data and match footage were synchronised using the SPRO™ to code players` physical performance and technical-tactical actions. A small statistically significant association was observed between HIA and players` actions with or without the ball (?2 = 183.27 (2, N = 4234), p<.001; Cramer`s V = 0.21). When players have the ball, the number of DEC efforts tends to increase with a corresponding decrease in ACC and HSR. When the players do not have the ball, ACC and HSR running tend to increase with a corresponding decrease in DEC. A comparison between HIA revealed that futsal performance requires greater mechanical efforts (ACC + DEC) than kinematic efforts (HSR). This underscores the importance of mechanical efforts within short space for futsal performance. Moreover, the diverse tactical actions associated with different player positions contribute to distinct activity profiles and physical requirements.